Sosialisasi Program Meningkatkan Semangat Belajar Anak Melalui Kegiatan Interaktif Di Surau Al Ikhlas Klang Lama Kuala Lumpur - Muhammad Hafiz; Murti Affiriani Hasibuan; Amanda sapitri; Muhammad Saleh (peduli riset dan pengabdian masyarakat, 2024)
The objects of this community service activity are children at Surau Al-Ikhlas Klang Lama Kuala Lumpur. The aim of carrying out this activity is to increase children's enthusiasm for learning through interactive activities, instilling positive attitudes from an early age. Activities carried out for the children of Al-Ikhlas Klang Lama Surau Kuala Lumpur include interactive game activities, quizzes, teaching and tutoring for children. The children of Al-Ikhlas Klang Lama Surau Kuala Lumpur are very enthusiastic about attending and taking part in a series of service activities This. The research method used was participatory observation and in-depth interviews with participants in this community service program. The research results show that through interactive activities children experience a significant increase in enthusiasm for learning. The implication of this research is the importance of an interactive approach in delivering educational programs to children to increase their enthusiasm for learning and involvement in the learning process.